Propagation dynamics and interaction of multiple streamers at and above adjacent dielectric pellets in a packed bed plasma reactor - Mujahid, Zaka-ul-Islam; Korolov, Ihor; Liu, Yue; Mussenbrock, Thomas; Schulze, Julian (Journal of Physics D: Applied Physics, 2022)
The propagation and interaction between surface streamers propagating over dielectric pellets in a packed bed plasma reactor operated in Helium are studied using phase and space resolved optical emission spectroscopy and simulations. Such a discharge is known to generate cathode directed positive streamers in the gas phase at the positions of minimum electrode gap followed by surface streamers that propagate along the dielectric surface. By systematically varying the gap between neighboring dielectric pellets, we observe that a larger gap between adjacent dielectric pellets enhances plasma emission near the contact points of the dielectric structures. In agreement with the experiment, the simulation results reveal that the gap influences the attraction of streamers towards adjacent dielectric pellets via polarization of the surface material and the repulsion induced by nearby streamers. For a smaller gap, the streamer propagation changes from along the surface to propagation through the volume and back to surface propagation due to a combination of repulsion between adjacent streamers, polarization of adjacent dielectric surfaces, as well as acceleration of electrons from the volume towards the streamer head. For a wider gap, the streamer propagates along the surface, but repulsion by neighboring streamers increases the offset between the streamers. The streamer achieves a higher speed near the contact point earlier in the absence of an adjacent streamer, which indicates the role of mutual streamer interaction via repulsion.